2023
DOI: 10.1177/11786361221150761
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Lactamase-Producing Gram-Negative Bacterial Isolates Among the Patients Attending a Tertiary Care Hospital, Kathmandu, Nepal

Abstract: Over the times, carbapenems have been the choice of drug for treating multidrug-resistant (MDR) and extended spectrum beta-lactamase (ESBL)-producing organisms. The current study aimed at determining the occurrence of metallo beta-lactamase (MBL) and AmpC beta-lactamase (ABL) in gram negative bacteria isolated from clinical samples. A cross-sectional study was conducted amongst the patients visiting Manmohan Memorial Medical College and Teaching Hospital (MMTH), Kathmandu, Nepal from August 2017 to January 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
1
0
0
Order By: Relevance
“…Further, the risk of isolating MDR E. coli in our study was noted from pus samples. Our findings are similar to reports from previous studies which reported a larger fraction of MDR E. coli from pus [ 162 , 163 ]. However, some studies revealed that urine had a high prevalence of MDR E. coli [ 164 , 165 , 166 , 167 , 168 ].…”
Section: Discussionsupporting
confidence: 93%
“…Further, the risk of isolating MDR E. coli in our study was noted from pus samples. Our findings are similar to reports from previous studies which reported a larger fraction of MDR E. coli from pus [ 162 , 163 ]. However, some studies revealed that urine had a high prevalence of MDR E. coli [ 164 , 165 , 166 , 167 , 168 ].…”
Section: Discussionsupporting
confidence: 93%